Penerapan Model Case-Based Learning terhadap Keterampilan Proses Sains dan Kemampuan Teknologi Informasi Siswa pada Materi Ekosistem: Penerapan Model Case-Based Learning - Kundera, I Nengah; Minarni; Lilies M.Tangge (Universitas Pendidikan Ganesha, 2025)
Science education in the digital era continues to face challenges in optimally developing students’ science process skills and information technology competencies. The lack of instructional models that effectively connect theoretical concepts to real-world contexts remains a barrier to achieving 21st-century competencies. This study aims to analyze the effectiveness of implementing the Case Based Learning (CBL) model in integrating students’ science process skills and information technology capabilities. This research employed a quantitative approach with a quasi-experimental design. The study involved 50 tenth-grade students divided into two groups: an experimental group and a control group. Data were collected using a science process skills test and an observation sheet to assess information technology skills. Data analysis was conducted using an independent sample t-test to determine significant differences between the two groups. The results revealed an increase in the average scores for both science process skills and information technology abilities. This improvement indicates that the CBL model encourages students to engage more actively, think critically, and relate learning to real-life situations. The findings conclude that the CBL model is effective in enhancing students’ science process skills and information technology competence. The implication is that CBL can be recommended as an innovative instructional strategy for science education that is contextual and aligned with the demands of the 21st century.